Biomass Waste Carbon Materials as adsorbents for CO2 Capture under Post-Combustion Conditions - Calvo-Muñoz, Elisa M.; García-Mateos, Francisco J.; Rosas, Juana M.; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2016)
A series of porous carbon materials obtained from biomass waste have been synthesized, with different morphologies and structural properties, and evaluated as potential adsorbents for CO2 capture in post-combustion conditions. These carbon materials present CO2 adsorption capacities, at 25°C and 101.3 kPa, comparable to those obtained by other complex carbon or inorganic materials. Furthermore, CO2 uptakes under these conditions can be well correlated with the narrow micropore volume, derived from the CO2 adsorption data at 0°C (VDRCO2). In contrast, CO2 adsorption capacities at 25°C and 15 kPa are more related to only pores of sizes lower than 0.7 nm. The capacity values obtained in column adsorption experiments were really promising. An activated carbon fiber obtained from Alcell lignin, FCL, presented a capacity value of 1.3 mmol/g (5.7%wt). Moreover, the adsorption capacity of this carbon fiber was totally recovered in a very fast desorption cycle at the same operation temperature and total pressure and, therefore, without any additional energy requirement. Thus, these results suggest that the biomass waste used in this work could be successfully valorized as efficient CO2 adsorbent, under post-combustion conditions, showing excellent regeneration performance.